Deputy Vice-Chancellor (A&I) appointed as MCDD Honorary Assistant Commissioner - Mohd Akram, Abdul Razak
Universiti Malaysia Pahang (UMP)’s Deputy Vice-Chancellor (Academic & International), Professor Ir. Dr. Badhrulhisham Abdul Aziz was appointed as Malaysia Civil Defence Department’s (MCDD) Honorary Assistant Commissioner, effective from July 3, 2012.